COMPARISON BETWEEN TITANIUM MINI PLATES VERSUS THREEDIMENSIONAL TITANIUM PLATES FOR FIXATION OF PALATAL FRACTURES (The Research of Medical Science Review, 2024)
OBJECTIVE: To compare the efficacy of 3-dimensional titanium plates versus mini titanium plates for the management of palatal fractures.METHODOLOGY: The randomized controlled trial was conducted in the Department of Dental Surgery at Liaquat University of Medical and Health Sciences (LUMHS), Jamshoro. The sample of 106 patients (53 in each group) selected using non-probability consecutive sampling. Patients aged 18–45 years of either gender who presented with isolated palatal fractures or palatal fractures associated with other facial fractures were included in the study. Patients were divided into two groups via lottery method: Group A treated with three-dimensional titanium plates and Group B with conventional miniplates. Both groups underwent surgical fixation under general anesthesia. Postoperatively, patients were prescribed standard antibiotics and analgesics for three days and were monitored clinically and radiologically at intervals of one week, one month, and three months. Efficacy was assessed at the final visit, 12 weeks postoperatively. SPSS version 26.0 was used to analyse the statistical data. RESULTS: The mean age of the participants was noted as 30.13 ± 5.14 years in the 3-DTM group and 31.30 ± 5.51 years. Gender distribution showed that 90.6% male participants in the 3-DTM group and 81.1% in the CTM group, while female participation was 9.4% and 18.9%. The 3-DTM group demonstrated significantly higher efficacy, with 73.6% achieving successful outcomes compared to 34.0% in the CTM group. The odds ratio for efficacy with 3-DTM was 5.417 (95% CI: 2.352–12.476), and this difference was highly statistically significant (p = 0.0001).CONCLUSION: The study demonstrated that 3D titanium plates were significantly more effective than mini titanium plates in stabilizing palatal fractures, ensuring better fracture stabilization, occlusal alignment, and anatomical reduction with fewer complications. More well-controlled prospective clinical trials are needed to validate the current findings.